New directions in cancer and aging: State of the science and recommendations to improve the quality of evidence on the intersection of aging with cancer control. Issue 9 (23rd February 2022) - Kobayashi, Lindsay C.; Westrick, Ashly C.; Doshi, Aalap; Ellis, Katrina R.; Jones, Carly R.; LaPensee, Elizabeth; Mondul, Alison M.; Mullins, Megan A.; Wallner, Lauren P.
Abstract : Background: The global population of older cancer survivors is growing. However, the intersections of aging‐related health risks across the cancer control continuum are poorly understood, limiting the integration of aging into cancer control research and practice. The objective of this study was to review the state of science and provide future directions to improve the quality of evidence in 6 priority research areas in cancer and aging. Methods: The authors identified priority research areas in cancer and aging through an evidence‐based Research Jam process involving 32 investigators and trainees from multiple disciplines and research centers in aging and cancer; then, they conducted a narrative review of the state of the science and future directions to improve the quality of evidence in these research areas. Priority research areas were defined as those in which gaps in scientific evidence or clinical practice limit the health and well‐being of older adults with cancer. Results: Six priority research areas were identified: cognitive and physical functional outcomes of older cancer survivors, sampling issues in studies of older cancer survivors, risk and resilience across the lifespan, caregiver support and well‐being, quality of care for older patients with cancer, and health disparities. Evidence in these areas could be improved through the incorporation of bias reduction techniques into longitudinal studies of older cancer survivors, novel data linkage, and improved representation of older adults in cancer research. Conclusions: The priority research areas and methodologies identified here may be used to guide interdisciplinary research and improve the quality of evidence on cancer and aging. Abstract : The population of older cancer survivors is growing, yet the effects of aging‐related health risks across the cancer control continuum remain poorly understood. This article identifies research areas that may be used to guide interdisciplinary research and improve the quality of evidence on cancer and aging.